Forages quality of Cenchrus clandestinum and Lolium perenne forages in the form of hay at different regrowth ages - Silva Déley, L.; Acosta, J.; Parra, G.; Martínez Freire, M.; Toro, B.; Sambache, J.; Peñafiel, S.; Chacón, E. (Cuban Journal of Agricultural Science, 2019)
In order to determine the chemical composition of Cenchrus clandestinum and Lolium perenne hay at different regrowth ages, a completely randomized design with three treatments and five repetitions was used for each of the species. The research was conducted in the province of Chimborazo, Ecuador. An amount of 30 male sheep of 25 kg average weight were used. Indicators of dry and organic matter, crude protein, crude fiber, neutral detergent fiber, acid detergent fiber, acid detergent lignin and ash were evaluated. Dry matter digestibility, organic matter, crude protein and crude fiber were determined. The highest dry matter value in Cenchrus clandestinum occurred at 50 days old with 93.98 %, and for protein it was at 30 days with 14.95 %. The highest percentage of fiber was presented at 50 days with 37.22. For Lolium perenne, the best result of dry matter was at 60 days with 87.23 % and the crude protein at 30 with 18.33 %. The highest values of neutral detergent fiber, acid detergent fiber and acid detergent lignin appeared at 60 days, with 63.70, 52.10 and 4.30 %, respectively. In specific cases of protein digestibility, the best results appeared after 30 days with 89.27 % for Cenchrus and 84.15 % for Lolium. The studied forages have an acceptable quality and chemical composition to be conserved as hay in the different evaluated regrowth ages. Key words: Cenchrus, digestibility, age, Lolium, protein